Montréal... l'histoire oubliée (Histoire Québec, 1996)
Keywords: Arts sacrés; Leduc, Ozias; Musées; Peinture; Églises

Du projet de reconquête économique à l'idée de management: un bilan des études consacrées au mouvement Desjardins - Rousseau, Yvan (Histoire sociale / Social History, 1996)
Keywords: Banques; Caisses populaires

100 ans d'histoire: revue de l'exercice 1991 - Association des banquiers canadiens (Association des banquiers canadiens, 1991)
Keywords: Banques

L'arme favorite de l'épicier indépendant: éléments d'une histoire sociale du crédit (Montréal, 1920-1940) - Taschereau, Sylvie (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1993)
Keywords: Épicerie

Le crédit dans une caisse populaire en milieu urbain: Saint-Alphonse d'Youville, 1940-1950 - Poirier, Jean (Université du Québec à Montréal, 1991)
Keywords: Banques; Caisses populaires; Saint-Alphonse-d'Youville (paroisse)

La fabrication des timbres-poste canadiens et des billets de banque à Montréal de 1871 à 1889: la British American Bank Note - Caron, Normand (Histoire Québec, 1996)
Keywords: Banques; Imprimerie; Poste

L'encadrement de la maternité au Québec entre les deux guerres: les gardes de La Métropolitaine, les Gouttes de lait et l'Assistance maternelle - Baillargeon, Denyse (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1990)
Keywords: Assistance maternelle; Assurance; Enfants; Femmes; Goutte de lait; Infirmières; La Métropolitaine

Prêtres et prêteurs au XIXe siècle - Hudon, Christine (Histoire sociale / Social History, 1993)

Desjardins et les Caisses Populaires 1900-1920, naissance et développement d'un mouvement coopératif - Poulin, Pierre (Université Laval, 1991)
Keywords: Banques; Caisses populaires; Desjardins, Alphonse

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

Par l'ordre et par l'économie. Les Caisses d'épargne et l'État au Québec (1819-1871) - Vanasse, Frédéric (Université du Québec à Montréal, 1991)
Keywords: Banques

La première caisse populaire de Montréal fut fondée par des leaders du mouvement ouvrier - Bélanger, Guy (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1998)
Keywords: Caisses populaires; Desjardins, Alphonse